2018
DOI: 10.1016/j.btre.2017.12.002
|View full text |Cite
|
Sign up to set email alerts
|

Effect of the Lippia alba (Mill.) N.E. Brown essential oil and its main constituents, citral and limonene, on the tracheal smooth muscle of rats

Abstract: HighlightsEOLa and citral promoted relaxation of tracheal smooth muscles in contractions induced by potassium and by acetylcholine.The effect of EOLa and citral on tracheal smooth muscles is mediate by reduction or absence of Ca2+ influx.Limonene less potent than EOLa and citral and does not act through voltage-operated cationic Ca2+ influx through channels.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

4
11
0

Year Published

2018
2018
2021
2021

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 27 publications
(15 citation statements)
references
References 16 publications
4
11
0
Order By: Relevance
“…Similar to our results, several monoterpenes have been suggested to block VOCCs in smooth muscles from various rat organs; these include citral in the aorta [31], 1,8-cineole, citral and limonene in the trachea [42,43], as well as citral and limonene in the uterus [44]. In addition, endogenous substances, such as progesterone and 5β-pregnanediol, have shown that VOCC inhibition is the main vascular relaxation route stimulated by these hormones in HUA vessels [33].…”
Section: Discussionsupporting
confidence: 89%
“…Similar to our results, several monoterpenes have been suggested to block VOCCs in smooth muscles from various rat organs; these include citral in the aorta [31], 1,8-cineole, citral and limonene in the trachea [42,43], as well as citral and limonene in the uterus [44]. In addition, endogenous substances, such as progesterone and 5β-pregnanediol, have shown that VOCC inhibition is the main vascular relaxation route stimulated by these hormones in HUA vessels [33].…”
Section: Discussionsupporting
confidence: 89%
“…In this model, contraction occurs through the binding of the agonist (PGF2α) to its receptor, also called prostanoid receptors or G protein-coupled receptors, that activates phospholipase C (PLC), and leads to an increase in intracellular Ca 2+ level and activation of protein kinase C (PKC), phosphatidylinositol-3-kinase (PI3K) and ERK1/2 in the human myometrium (Heppelmann et al, 2018;Xu et al, 2015). Considering reports in the literature, citral also can inhibit the contractions of the tracheal smooth muscle of rats by reduction of Ca 2+ influx (Carvalho et al, 2018); in fact, some chemical compounds from essential oils, such as citral, geranial or lemongrass, have been shown to have vascular relaxant effects in different experimental models of cardiovascular diseases, such property has been related to the blockade of Ca 2+ influx (de Andrade, Brasil, Endringer, da Nobrega, & de Sousa, 2017). These data are consistent with our results, citral also can inhibit PGF2α-induced contractions in the human myometrium, an effect which could also be related to the blockade of the calcium channels, as reported in the studies mentioned above.…”
Section: Discussionmentioning
confidence: 99%
“…The pharmacological potential of Lippia alba essential oils has been widely described in the literature [13,17,32]; however, its action on Gram-negative bacteria of medical importance has been little explored. The present study demonstrated the excellent antimicrobial potential of this oil on strains causing gastrointestinal infections.…”
Section: Discussionmentioning
confidence: 99%